(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2025)
This study is dedicated to a comprehensive analysis of citizen involvement in ensuring public safety in the People’s Republic of China (PRC), with an emphasis on theoretical foundations and practical applications of legal regulatory mechanisms. The focus is on key legislative acts that govern the interaction between state institutions and public organizations, including such fundamental documents as the PRC laws "On National Security" and "On Counter-Terrorism." The study examines mechanisms of citizen participation, among which the activities of residents’ committees, auxiliary police units, and digital innovations—particularly the social credit system—are evaluated as tools for optimizing public safety. Based on an analysis of statistical data and expert opinions, the functionality and effectiveness of these mechanisms are studied, highlighting their advantages and identifying limitations.